Manifestations of Realistic Personality in Saadallah Wannous's Rape Play (Journal of the College of Basic Education, 2025)
The events of the play take place in two different spaces: the Palestinian where Al-Fara'a and Dalal and the Palestinian sorrow, and the Israeli security raids on Palestinian homes, arresting their youth and raping their women. In this play, there are two narrators and two stories, an Israeli narrator and a Palestinian narrator, an Israeli story and a Palestinian story. The events overlap and intersect at three points: rape, arrest, and collision. The first story is narrated on the same level. The content is the story of the Palestinian freedom fighter Ismail and his family members when he was arrested and castrated in prison, after which his wife, Dalal, was raped in front of his eyes. This event made her realize the barbarism and brutality of the occupation so.